Korean American Adolescent Depression and Parenting - Kim, Eunjung (2008)
PROBLEM: Korean American adolescents tend to experience more mental health problems than adolescents in other ethnic groups. METHODS: The goal of this study was to examine the association between Korean American parent-adolescent relationships and adolescents’ depressive symptoms in 56 families. FINDINGS: Thirty-nine percent of adolescents reported elevated depressive symptoms. Adolescents’ perceived low maternal warmth and higher intergenerational acculturation conflicts with fathers were significant predictors for adolescent depressive symptoms. CONCLUSIONS: The findings can be used to develop a family intervention program, the aim of which would be to decrease adolescent depressive symptoms by promoting parental warmth and decreasing parent-adolescent acculturation conflicts.